Finding people like me: contact among young adults who share an open-identity sperm donor. Issue 4 (23rd December 2020) - Scheib, J E; McCormick, E; Benward, J; Ruby, A
Abstract: STUDY QUESTION: What interests and experiences do donor-conceived adults have with respect to same-donor peers/siblings, when they share an open-identity sperm donor? SUMMARY ANSWER: Donor-conceived young adults report considerable interest in, and primarily positive experiences with, their same-donor peers, with some finding 'people like me'. WHAT IS KNOWN ALREADY: Through mutual-consent contact registries, director-to-consumer DNA testing and other means, donor-conceived people with anonymous (i.e. closed-identity) sperm donors are gaining identity-related information from, and establishing relationships with, people who share their donor. STUDY DESIGN, SIZE, DURATION: Semi-structured, in depth telephone and Skype interviews with 47 donor-conceived young adults were carried out over a 31-month period. Inclusion criteria were being one of the first adults for each donor to obtain their identity and being at least 1-year post donor-information release. PARTICIPANTS/MATERIALS, SETTING, METHODS: Participants (aged 19–29 years, 68.1% women) were born to female same-sex couple parents (46.8%), a single mother (29.8%) or heterosexual couple parents (23.4%); all parents had conceived through the same US open-identity sperm donation program. The dataset was analyzed thematically and included interviews from only one participant per family. Each participant had a different donor. MAIN RESULTS AND THE ROLE OF CHANCE: Interest in, and experiences with, same-donor peers suggested that they occupy a unique position in the lives of donor-conceived young adults who share their open-identity donor. Contact can provide identity-relevant information and support through the availability of relationships (whether actualized or potential), shared experiences, and easier relationships than with their donor. Most donor-conceived young adults felt positively about their contact experiences. Of those not yet linked, almost all expressed an interest to do so. Some had met the children raised by their donor. When asked, all expressed an interest in doing so. LIMITATIONS, REASONS FOR CAUTION: Interviews were conducted with donor-conceived young adults who were uncommon in their generation in terms of: having an open-identity sperm donor; the majority knowing about their family's origins from childhood; and having parents that accessed at the time one of the only open-identity sperm donation programs. Further research is needed to assess applicability to all donor-conceived adults; findings may be more relevant to the growing number of people who have an open-identity donor and learned in childhood about their family's origins. WIDER IMPLICATIONS OF THE FINDINGS: Participants were among the first generation of donor-conceived adults with an open-identity sperm donor. Their experiences and perspectives can provide essential guidance to programs and others with similar origins. Early disclosure of family origins and identifying the donor did not diminish the young adults' interest in their same-donor peers. Positive experiences suggest that the benefits of contact include not only identity-relevant information (through shared traits and experiences), but also relationships with and support from people who understand the uncommon experience of being donor conceived. Implications include the need to educate families and intended parents about the potential benefits of knowing others who are donor conceived, and the risk of unexpected linking across families by donors, regardless of donor-conceived person or family interest. STUDY FUNDING/COMPETING INTEREST(S): The study was funded by the Lesbian Health Fund of GLMA: Health Professionals Advancing LGBTQ Equality. The authors have no conflict of interest to declare.